HUBUNGAN TINGKAT PENGETAHUAN IBU DENGAN PEMBERIAN ASI EKSKLUSIF DI PUSKESMAS TANJUNG MORAWA - Simanjuntak, Maesstro Bina Utama; Situmeang, Ivonne Ruth Vitamaya Oishi; Amalia, Rizky; Depari, Angelica Sembiring; Simbolon, Helen Emsita; Priskila, Erleena (Universitas Methodist Indonesia, 2023)
In order to reduce infant morbidity and mortality, according to the United Nations Childrens Fund (UNICEF) and the World Health Organization (WHO), it is recommended that infants be fed only breast milk for six months, known as exclusive breastfeeding. Exclusive breastfeeding in Indonesia has not been fully successful. Based on the 2016 Indonesian Health Profile, the percentage coverage of exclusive breastfeeding for infants aged 0-6 months was only 54.0%. In North Sumatra Province, exclusive breastfeeding is considered to be lacking. Factors that are thought to influence include maternal age, education level, knowledge level and occupation. So, an observational analytic study was conducted which aimed to see the relationship between the level of maternal knowledge and exclusive breastfeeding. The results showed that there was a significant relationship between maternal knowledge level and maternal education level with exclusive breastfeeding for infants.